PENAPISAN BAKTERI SIMBION LAMUN Thalassia hemprichii PENGHASIL ENZIM HIDROLASE - Rizky I. Moroki; Elvy L. Ginting; Stenly Wullur; , Sandra Tilaar; Veibe Warouw; Edwin L.A. Ngangi (Sam Ratulangi University, 2022)
The research aims to determine the ability of the seagrass symbiont bacteria Thalassia hemprichii to produce protease and amylase. The symbiont bacteria T. hemprichii had been cultured in the laboratory. Five isolate bacteria namely 3M.2, E2.2, E3.2, 6.2 and 5.2 were analyzed in this research. Bacterial enzyme activity was screened by growing the bacterium using the paper disc on skim milk agar and starch agar media for 2 x 24 hours. Enzyme activity was indicated by the formation of a clear zone around the bacterial colonies. The proteolytic (IP) and amylolytic indexes (IA) were calculated by dividing the diameter of clear zone with the bacterium colonies. The results showed that the bacterial isolate 3M.2, E2.2 and 6.2 could produce proteases in 24 hours incubation with IP of 1,67, 1,20 and 1,33, respectively. While isolate 5.2 could produce protease after being incubated for 48 hours with an IP of 1,03. During the 48 hours incubation time, there were decrease in the IP of bacterial isolates of 3M.2, E2.2 and 6.2. Furthermore, 3M.2 bacterial isolate was able to produce amylase in 24 hours of incubation with an IA of 1,27. Meanwhile, bacterial isolate E2.2 could produce amylase after being incubated for 48 hours with an IA of 1,17. Keywords: Seagrass T. hemprichii, hydrolase enzymes, amylase, protease ABSTRAK Penelitian ini bertujuan untuk menentukan kemampuan bakteri simbion lamun Thalassia hemprichii dalam menghasilkan enzim protease dan amilase. Sampel bakteri yang diuji merupakan bakteri yang telah dikultur di Laboratorium, berjumlah 5 isolat yakni 3M.2, E2.2, E3.2, 6.2 dan 5.2. Pengujian aktivitas enzim bakteri dilakukan dengan menumbuhkan bakteri pada media skim milk agar dan media amilum selama 2 x 24 jam dengan menggunakan metode kertas cakram. Aktivitas enzim ditandai dengan terbentuknya zona bening di sekitar koloni bakteri yang tumbuh, dan selanjutnya dihitung indeks proteolitik dan amilolitik. Hasil penelitian menunjukkan bahwa isolat bakteri 3M.2, E2.2 dan 6.2 dapat menghasilkan protease selama waktu inkubasi 24 jam dengan IP sebesar 1,67 dan 1,20 dan 1,33 secara berurutan. Sedangkan isolat 5.2 dapat menghasilkan protease setelah diinkubasi selama 48 jam dengan IP sebesar 1,03. Pada waktu inkubasi 48 jam, terjadi penurunan IP dari isolat bakteri 3M.2, E2.2 dan 6.2. Isolat bakteri 3M.2 mampu menghasilkan amilase pada waktu inkubasi 24 jam dengan IA sebesar 1,27, sedangkan isolat bakteri E2,2 dapat menghasilkan amilase setelah diinkubasi selama 48 jam dengan IA sebesar 1,17. Kata Kunci : Lamun T. hemprichii, enzim hidrolase, amilase, proteas